Anthropometric indices, blood pressure, and lipid profile status among women using progestin-only contraceptives: comparative cross-sectional study - Mulu Shiferaw; Woldeteklehaymanot Kassahun; Belay Zawdie (BMC, 2021)
Abstract Background The major types of hormonal contraception used currently in Ethiopia are progestogen-only. This study aimed to assess the differences in anthropometry indices, blood pressure, and lipid profile among women using progestin-only contraceptives in selected health facilities of Jimma town, southwest Ethiopia. Methods A facility-based comparative cross-sectional study was conducted among women of reproductive age using Depo-medroxyprogesterone acetate (DMPA) and implant in selected health facilities from April 11 to May 11, 2019. A total of 146 women (45 DMPA and 51 implant users and 50 non-users) were selected randomly for inclusion in the study. One-way analysis of variance was used to examine variations in health outcomes while Bonferroni post-hoc tests were conducted to determine significance of variations between multiple outcomes. Results There was a statistically significant difference in the mean Body Mass Index (p = 0.045), Hip-to-waist ratio (p = 0.012), systolic blood pressure (p = 0.027), diastolic blood pressure (DBP) (p = 0.017), total cholesterol (TC) (p = 0.005), low-density lipoprotein (p = 0.023) and triacylglycerol (TAG) (p = 0.000) between women using progestin-only contraceptives and non-users. DMPA users had higher TC (p = 0.024) than non-users. Results from Pearson correlation analysis showed that DBP of DMPA users was higher with longer duration of use. Conclusion The findings suggest the need for family planning service providers to undertake appropriate client profiling before recommending a particular method to women seeking the services in order to minimize adverse health risks, especially for those who may have pre-existing conditions.